Use of Ohmic Heating System in Meat Thawing and Its Effects on Microbiological Quality - Duygu Balpetek Külcü; Ümit Gürbüz (MANAS: Journal of Engineering)
This study was conducted to determine theapplication of the ohmic heating system in meat thawing process and its effectson the microbiological quality of the meats. For this purpose, traditionalthawing methods (room temperature and refrigerator) are compared with the ohmicsystem. Beef loin (Longissimus lumborum,LL) was used as the material in theexperiments by cutting into 5x10cm pieces. The samples were divided into threegroups by taking the thawing methods into consideration. The grouped meatsamples were frozen at -35±1°C for 24 hours and stored at -18°C for 6 months.During the storage period, changes in color (L*,a*,b*) and microbiologicalcondition of the samples were determined periodically throughout the storageperiod. In all experimental meat samples thawed by different methods,considering the period of frozen storage; There were statistically significantdifferences in total microorganism, Pseudomonas spp and coliform numbers afterthe second month (p<0.05). It was also observed that decreases observed inthe number of yeast-mould during storage period were not significant(p>0.05). When the thawing methods applied in this study evaluated in termsof L*, a*, b* values, there was no statistically difference between the groups(p> 0.05). As a result, it has been concluded that the ohmic heating systemcan be used as an alternative method for thawing frozen meat.